RWI-UNI-SUBJECTS: Complete records of all subjects across German HEIs (1971-1996) - Friederike Hertweck; Lukas Jonas; Boris Thome; Serife Yasar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
The dataset RWI-UNI-SUBJECTS provides comprehensive information on the universe of academic subjects offered by the universe of higher education institutions across Germany between 1971 and 1996. RWI-UNI-SUBJECTS is based on tables extracted from paper-based guides on "Study and Career Choice'' that are annually published by the Federal Employment Agency to inform high school students about post-secondary education. The dataset is available on request as a public-use file from the Research Data Center Ruhr (FDZ Ruhr). It is structured to easily link locations, universities, and subjects with administrative and survey data. This dataset holds significant potential for use across various disciplines, including history, sociology, political science, economics, and other fields analyzing the higher education market. – – Der Datensatz RWI-UNI-SUBJECTS bietet eine umfassende Informationsbasis zum Fächerangebot an allen Hochschulen in Deutschland für den Zeitraum 1971 bis 1996. Der Datensatz basiert auf Tabellen aus den "Handbüchern zur Studien- und Berufswahl". Diese Handbücher werden jährlich von der Bundesagentur für Arbeit herausgegeben, um Abiturientinnen und Abiturienten über die Möglichkeiten eines Hochschulstudiums zu informieren. Der Datensatz kann als Public Use File beim Forschungsdatenzentrum Ruhr (FDZ Ruhr) angefordert werden. Die Datenstruktur erlaubt eine einfache Verknüpfung von Standorten, Hochschulen und Fächern mit administrativen und Befragungsdaten. Der Datensatz bietet ein hohes Nutzungspotenzial in verschiedenen Disziplinen, darunter Geschichte, Soziologie, Politikwissenschaft, Wirtschaftswissenschaft und viele andere Forschungsbereiche, die den Hochschulmarkt untersuchen.
Keywords: I20; I23; J24; 330